2018
DOI: 10.1016/j.ejor.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

A sequential stochastic mixed integer programming model for tactical master surgery scheduling

Abstract: In this paper, we develop a stochastic mixed integer programming model to optimise the tactical master surgery schedule (MSS) in order to achieve a better patient flow under downstream capacity constraints. We optimise the process over several scheduling periods and we use various sequences of randomly generated patients' length of stay scenario realisations to model the uncertainty in the process. This model has the particularity that the scenarios are chronologically sequential, not parallel. We use a very s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…At the microscale, they involve how the beds are configured, how the patients are placed, and how patients are admitted to the hospital. Relevant scholars have investigated and evaluated bed utilization efficiency in a certain area in Canada [ 16 , 17 ]. The study found that, of the 2007 patient study subjects, 14.2% of patients did not meet the admission criteria, and the total length of hospital stay was 14,194 days, of which 22.8% were unreasonable.…”
Section: Introductionmentioning
confidence: 99%
“…At the microscale, they involve how the beds are configured, how the patients are placed, and how patients are admitted to the hospital. Relevant scholars have investigated and evaluated bed utilization efficiency in a certain area in Canada [ 16 , 17 ]. The study found that, of the 2007 patient study subjects, 14.2% of patients did not meet the admission criteria, and the total length of hospital stay was 14,194 days, of which 22.8% were unreasonable.…”
Section: Introductionmentioning
confidence: 99%
“…There are a variety of methods developed for tackling the uncertainties in surgical scheduling, among which the most common two are stochastic optimization and robust optimization . For the former, Kumar et al ( 2018 ) develop a stochastic mixed-integer programming model to balance the patient flow under downstream capacity constraints. Stochastic optimization considers hospitalization time to be stochastic, but assumes that the distribution is known, which might not be true in practice.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Surgery types are often sets of surgeries that are similar in economic and resource usage perspective. This is the case in, e.g., Bovim et al (2020); Anjomshoa et al (2018); Kumar et al (2018); Dellaert and Jeunet (2017); Visintin et al (2016); Cappanera et al (2014); Banditori et al (2013);van Oostrum et al (2008). Once again, decisions on how much operating room time to assign to each specialty are not usually considered or do not take into account issues such as equity or waiting list length.…”
Section: Literature Reviewmentioning
confidence: 99%